RESPON PERTUMBUHAN DAN HASIL KACANG HIJAU (Vigna radiata L.) TERHADAP PUPUK KANDANG SAPI - Maswiruddin, Maswiruddin; Zuhry, Elza; Adiwirman, Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The research aims to study the growth and yield of green beans from the provision of cow manure. The research was conducted at the Experimental Station of the Faculty of Agriculture, University of Riau, Pekanbaru from February to April 2018. Completely Randomized Design (CRD) was used in this experiment, with three replications. The cow manure treatment consists of five levels A = No Cow Manure, B = 5 tons. ha-1, C = 10 ton. ha-1, D = 15 tons. ha-1 and E = 20 ton. ha-1. The parameters observed were planted height, number of primary branches, age of flowering plants, harvest age, the number of plant pods, percentage of pithy pods, seed weight per m2 and weight of 1000 seeds. The results showed that green bean plants did not respond to the cow manure application and the nutrient requirements have been fulfilled from the application of Urea, TSPand KCl fertilizer. Keywords: cow manure, green bean,growth and yield.